Comparison of solvent and techniques for extraction of benzophenone from paper intended to come into contact with foodstuffs - Saesaengseerung, Neungrutai (Bulletin of Applied Sciences, 2016)
Benzophenone is used as a photo-initiator in UV cure ink for printing of packaging. Basically, colorful paper packaging may be contaminated with high concentration of benzophenone. If the paper is extracted using inappropriate method, extracted benzophenone might be less than the actual amount. Therefore, to obtain the efficiency of extraction, Chinese cake paper box contaminated with benzophenone in high concentration was selected as test sample. The sample was extracted using various solvent, including acetonitrile, ethanol and mixture of dichloromethane and three kinds of solvents, such as cyclohexane, hexane and acetronitrile in the ratio of 1:1. This study found that the extracted paper sample using 95% ethanol gave the highest yield of benzophenone. The yield form 95% ethanol extraction is around 7% higher than those from acetronitrile and acetronitrile: dichloromethane (1:1) and around 5096 yield higher than those from the mixture of dichloromethane and cyclohexane or hexane used. Furthermore, the results of extracted benzophenone by varying extraction techniques: at room temperature for 24 hr, 60°C for 2 hr in water bath and temperature below 60°C ultrasonic bath were 308, 322 and 320 mg/kg, respectively. Although these results are not significantly different at 95% confidences (One Way Anova, p = 0.397), ultrasonic extraction gave the least standard deviation (n=3). In conclusion, the appropriate technique for benzophenone extraction from food contact paper is ultrasonic extraction using 95% ethanol as extraction solvent.